1992
DOI: 10.1099/0022-1317-73-12-3219
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to phloem transport of potato leafroll virus in potato plants

Abstract: A 'double-graft sandwich' technique in which sections of potato stem from different potato cultivars were grafted between a susceptible healthy stock plant and a potato leafroll virus (PLRV)-infected scion was used to study the rate of phloem transport of PLRV in cultivars differing in resistance to PLRV infection (I R) and accumulation (AR). Resistance to phloem transport (i.e. delayed PLRV systemic movement) was found in Bismark cultivar (I R AS). This was independent of I R and A R as the rate of movement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
1
26
1
1
Order By: Relevance
“…In our experiments, the movement of PLRV through two graft unions began around 7 days after grafting and was generally complete by about 14 to 16 days, though in some experiments, virus movement was slightly slower. Very similar estimates were made by Wilson & Jones (1992). Movement of virus through grafts occurred soon after acquiring functional phloem continuity across grafts as demonstrated by 6(5)-carboxyfluorescein tracing (around 7 days after grafting ; Table 1).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…In our experiments, the movement of PLRV through two graft unions began around 7 days after grafting and was generally complete by about 14 to 16 days, though in some experiments, virus movement was slightly slower. Very similar estimates were made by Wilson & Jones (1992). Movement of virus through grafts occurred soon after acquiring functional phloem continuity across grafts as demonstrated by 6(5)-carboxyfluorescein tracing (around 7 days after grafting ; Table 1).…”
Section: Discussionsupporting
confidence: 65%
“…It is, therefore, likely that neither the H-MR nor T-MR mechanisms present in the tested clones cause a slowing of PLRV movement along phloem strands. In similar experiments, Wilson & Jones (1992) observed that test stem pieces of potato cv. Bismark did reduce the rate of PLRV movement and suggested that this was possibly the result of the severe necrosis associated with PLRV infection in this cultivar.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations